Cardiovascular effects of increasing dosages of norepinephrine in healthy isoflurane-anesthetized New Zealand White rabbits. (November 2020) - Uccello, Olivia; Sanchez, Andrea; Valverde, Alexander; Beaufrère, Hugues
Abstract: Objective: To characterize the cardiovascular effects of increasing dosages of norepinephrine (NE) in healthy isoflurane-anesthetized rabbits. Study design: Prospective experimental study. Animals: A total of nine female ovariohysterectomized New Zealand White rabbits weighing 3.4 ± 0.2 kg (mean ± standard deviation). Methods: Rabbits were premedicated intramuscularly with buprenorphine (0.05 mg kg –1 ) and midazolam (0.5 mg kg –1 ). Anesthesia was induced with intravenous propofol and maintained with a 1.1 × minimum alveolar concentration of isoflurane for this species to induce hypotension. Rabbits were administered NE infusions at three doses: low, 0.1 μg kg –1 minute –1 ; medium, 0.5 μg kg –1 minute –1 ; and high doses, 1 μg kg –1 minute –1 for 10 minutes each in that order. Cardiovascular variables including heart rate (HR), cardiac output (CO) by lithium dilution technique and systolic (SAP), mean (MAP) and diastolic (DAP) invasive arterial blood pressures measured in the auricular artery were recorded at baseline, 10 minutes after the start of the infusion of each NE treatment and 10 minutes after NE was discontinued. A linear mixed model and a type III anova with Tukey's post hoc comparison was performed ( p < 0.05). Results: Significant increases in SAP (28% and 90%), MAP (27% and 90%) and DAP (33% and 97%) were measured with medium and high dose treatments, respectively ( p < 0.001), with no changes in CO. HR decreased and stroke volume increased significantly with high dose treatment (by 17% and 15%, respectively; p < 0.05). No arrhythmias were noticed with NE treatments. Conclusions and clinical relevance: The infusion of NE at 0.5–1.0 μg kg –1 minute –1 is a potentially effective treatment for hypotension in healthy isoflurane-anesthetized New Zealand White rabbits.